The Impact of Green Innovation on Corporate Sustainability Performance: A Case Study of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Malang City, Indonesia - Arga Bayu Rachman; Anthon Efani; Dini Atikawati (Postgraduate, University of Mataram, 2025)
This research assesses the impact of green innovation on the sustainable performance of micro, small, and medium-sized enterprises (MSMEs) in Malang City using a systematic and empirical approach. Employing Structural Equation Modeling-Partial Least Squares (SEM-PLS), the study analyzes several antecedent variables and their effects on green innovation, emphasizing employee conduct and government pressure as significant drivers. Data collection was conducted through Likert-scale questionnaires and Focus Group Discussions (FGDs) involving MSME practitioners and local government officials. A quantitative explanatory approach employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze data from 216 purposively sampled MSME respondents via Likert-scale questionnaires, supplemented by Focus Group Discussions (FGDs) with practitioners and local officials. The model assessed outer and inner validity, reliability, path coefficients, R-square values (0.647 for green innovation, 0.718 for sustainable performance), and bootstrapping for hypothesis testing. Employee conduct (path coefficient = 0.344, p=0.000) and government pressure (path coefficient = 0.317, p=0.000) significantly drive green innovation, which strongly enhances sustainable performance (path coefficient = 0.650, p=0.000). Environmental dynamics positively affect sustainable performance (path coefficient = 0.195, p=0.002) but negatively moderate the green innovation–sustainable performance link (path coefficient = -0.094, p=0.009), indicating instability weakens benefits amid regulatory and environmental changes. These findings highlight internal behaviors and policy enforcement as key levers over technological or competitive factors in resource-constrained MSMEs. Prioritizing employee pro-environmental engagement and government regulatory support fosters green innovation for improved MSME sustainability, while building adaptive strategies helps counter environmental dynamism; these insights guide policymakers and owners toward integrated environmental–economic strategies.